SERVICES MARKETING STRATEGIES AND CUSTOMER LOYALTY: MEDIATING AND MODERATING ROLE OF CUSTOMER SATISFACTION AND LOCATION - SALEH DUTSENWAI, HAUWA (2015)
The dynamic market environment and intense competition has forced the petrol stations to become more competitiveto sustain their market locally and internationally. Businesses are engaged in marketing strategies to improve business performance to satisfy customers and develop loyalty. Customer loyalty is one of the important approaches for retailers to improve competitive edge. Despite the importance of customer loyalty, some retail stores lacked in service quality, product quality, and customer satisfaction whereas need comprehensive measures to explain how customers become loyal to a particularbrand. Many empirical studies have centered on marketing strategies/factors influencing customer satisfaction and loyalty in different industries, but this is lacking in the petrol stations business.